Efektivitas Asap Cair Limbah Kulit Buah Siwalan dan Tongkol Jagung terhadap Pengawetan Kayu Sengon Berdasarkan Massa Jenis dan Kadar Air - Anggraini, Desti Nur; Setyaningrum, Sulis; Khoiriyan, Muhamad Wisnu; Rahayu, Desta Putri; Mulyaningrum, Eko Retno (BIOEDUSCIENCE, 2024)
Background: Sengon is a fast-growing plant harvested 5-7 years after planting and is easily attacked by termites, so it needs to be preserved. Siwalan fruit husks and corn cobs are usually thrown away without being processed into useful products, even though these materials contain lignin, cellulose, and phenolics, which have the potential to act as anti-termite substances. To determine the potential of liquid smoke from siwalan husk and corn cob waste as a preservative for sengon wood ( Paraserianthes falcataria). Methods: This research was conducted at the Biology Laboratory, Campus 3, PGRI University, Semarang, in September 2023. The research method was RAL (Completely Randomized Design) 9 treatments with three repetitions, namely: P0 (control), 5% liquid smoke from palm fruit husk waste (P1), 10% (P2), 15% (P3), and 20% (P4). Next, corn cob liquid smoke was 5% (P5), 10% (P6), 15% (P7), and 20% (P8). Results: The best increase in wood density was treatment P8, P1, P2, P5, P0, P3, P4, P6, and P7. The best increase in water content of sengon wood is in formulas P8, P4, P2, P6, P7, P1, P0, P5, and P3. The concentration of corncob liquid smoke contains the highest total Cr and dissolved Fe compounds compared to distilled water and liquid smoke from siwalan fruit peel waste, so it can potentially preserve sengon wood. Conclusions: liquid smoke from siwalan fruit peel and corn cob waste can be used as a preservative for sengon wood.